Augmented Reality as A Learning Media Based on Scientific Literacy - Damayanti, Depi; Susetyarini, Rr Eko; Wahyono, Poncojari (Jurnal Biotek, 2025)
The development of digital technology has brought about a transformation in the world of education, which is now leading to the use of technology to enrich the learning process. One of the technological innovations that has great potential in education is Augmented Reality (AR). This study aims to examine the use of Augmented Reality as a learning medium that can improve students' scientific literacy, especially in understanding complex scientific concepts. Another objective is to find out how AR can increase students' interest, motivation, and involvement in the learning process. This finding uses the Systematic Literature Review (SLR) method, which is carried out by identifying, selecting, and analyzing various previous studies on the application of AR in science learning. Data were obtained from various academic databases such as Google Scholar, ScienceDirect, and JSTOR. Clear inclusion and exclusion criteria were used to select relevant findings and make significant contributions to understanding the effectiveness of AR in science education. The results of the literature analysis indicate that the use of AR in science learning can improve students' understanding of abstract concepts and enrich their learning experience. AR provides a more engaging and interactive learning experience, which can increase student motivation and involvement. In addition, AR also supports various learning styles, such as visual, kinesthetic, and auditory, thus helping students understand science materials more deeply and contextually. However, several challenges related to infrastructure, teacher readiness, and costs are still obstacles to implementing AR in schools.